Music and physical activity in early childhood: the ambiguous role of the at-home context and extracurricular activities - Lucendo-Noriega, Alicia; Sääkslahti, Arja; Ansani, Alessandro; Henttonen, Katariina; Carlson, Emily; Saarikallio, Suvi Helinä; Toiviainen, Petri; Linnavalli, Tanja (Frontiers in Psychology, 2026)
IntroductionThis exploratory, cross-sectional study investigates how music and physical activity (PA) engagement at home, and attendance in music and PA based extracurricular activities are associated with children’s verbal fluency (word generation and sentence repetition), inhibitory control, emotion recognition, music and motor skills.MethodsParticipants (N = 103) were from 10 early childhood centers in a Finnish mid-size city and completed the related measurements in the school settings at a mean age of 49 months (SD = 3.5).ResultsA positive association between attendance in music as extracurricular activity and the word generation test was observed. Interestingly, an opposite trend between the reported use of physical activity at home and the sentence repetition score was noted. Lastly, a surprising association was observed as the children with the highest amount of music and PA at home scored the lowest in the emotion recognition measure.DiscussionFurther longitudinal data is needed to explore the preliminary trends observed in this data. Future research should also consider other types of direct-measures and contextual factors. Nonetheless, the results emphasize the need to explore how the early context and experiences might impact children’s development, and how to better support them through diverse activities, such as physical activity and music.